The limits of anaerobic glycolytic capacities of skilled wrestlers on the basis of anaerobic testing loads of different duration and character - Sawczyn, S.; Lusenko, O. N.; Mishchenko, V. S.; Pasek, M.; Dornowski, M. (Archives of Budo, 2017)
Background and Study Aim: It is known that a fatigue response underlies the efficient of elite wrestlers` specific work capacities. Differences in fatigue and characteristics of special work capacity may relate to differ in capacities of anaerobic lactate systems. The objective of the study was the maximal individual level of anaerobic glycolytic capacities of skilled wrestlers based on the results of three variants of a specific laboratory test.